Fonctionnalisme et thérapeutique - Gadet, Françoise (Cahiers du Centre de Linguistique et des Sciences du Langage, 2022)
Françoise GADET, University of Paris-X-Nanterre : «Functionalism and therapeutics» At about the same time (around 1930) a number of works written by different linguists, representing various schools of thought in various countries, all highlight a concern with language change and in particular with the notion of causality (Jakobson, Frei). Each in his own way is aiming to develop a functionalist perspective on a system, in which teleology and function will play – in varying degrees – an important part, thorough the incorporation of the idea of the «speaking subject». This article starts from a close reading of Jakobson and uses current notions of language change, in order to shed light on the relation between Jakobson's work and that of other linguists in the 1930s.